Visual Quality of the Facade of Cultural Heritage Buildings in the Historic Area of Jalan Semeru Malang City - Faisal Bahar; Herry Santosa; Jenny Ernawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Jalan Semeru Malang City is one of the historical areas that plays an important role in the development of the western part of Malang City which has many historical buildings from the Dutch colonial heritage. The purpose of this study was to find out the similarities and differences in perceptions between the public and practitioners and academics in the field of architecture in assessing the visual elements on the facades of cultural heritage buildings, as well as to find out the visual elements of the facades that were significant according to the public, practitioners and academics in the field of architecture on the visual quality of the facades of historic buildings along the way. the corridor of Jalan Semeru Malang City. The development and construction along the Jalan Semeru corridor, Malang City, which does not pay attention to the context of the area as a historic area, can slowly cause a shift in the shape and meaning of the city structure which can affect the visual character of building facades in the area. The shift in the visual character of the building facade that does not pay attention to the regional context in a historic area can have a negative impact on environmental aesthetics, causing a decrease in the visual quality of the historic area. This study uses quantitative research methods with a public perception approach. To measure people's perceptions, a differential semantic scale is used which contains two opposite words. The results of this study indicate that the assessment between two groups of respondents with different occupational and educational backgrounds has different assessment results on each facade element. Facade elements that are significant to the visual quality